Simplify (9x ^ 2 - 6x + 2) - (x ^ 2 + 4x - 39) (1 point)

1 answer

To simplify the expression \((9x^2 - 6x + 2) - (x^2 + 4x - 39)\), we can follow these steps:

  1. Distribute the negative sign across the terms in the second parentheses: \[ (9x^2 - 6x + 2) - x^2 - 4x + 39 \]

  2. Combine like terms:

    • Combine \(9x^2\) and \(-x^2\): \[ 9x^2 - x^2 = 8x^2 \]
    • Combine \(-6x\) and \(-4x\): \[ -6x - 4x = -10x \]
    • Combine the constants \(2\) and \(39\): \[ 2 + 39 = 41 \]

Putting it all together, we get: \[ 8x^2 - 10x + 41 \]

So, the simplified expression is: \[ \boxed{8x^2 - 10x + 41} \]

Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions